Plurality is a conditio per quam of all political life - Bojanić Sanja (Filozofija i Društvo, 2020)
The book Phenomenology of Plurality: Hannah Arendt on Political Intersubjectivity is a contribution not only to the phenomenological tradition of thought and Hannah Arendt studies, but also political science and, most importantly, political philosophy. Sophie Loidolt advances an intervention that stands in contrast to contemporary phenomenological research which in certain times have had the tendency to perform depoliticized examination of the self and sociality, actually revealing the intention of Phenomenology of Plurality to articulate the numerous elements that comprise the methodological novelty with which Arendt changes the theory of the political.